Molecular characterization and effectiveness cross-protection of weak strains against super-infection malignant strains Cucumber mosaic virus (CMV) on cayenne pepper (Capsicum annuum L.) in Lampung, Indonesia - Mahfut, Mahfut; Sari, Mai; Akin, Hasriadi Mat; Wahyuningsih, Sri; Irawan, Bambang (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Cayenne pepper (Capsicum annuum L.) is a horticultural crop of significant economic importance. One of the major threats to its cultivation is the Cucumber mosaic virus (CMV), which can cause severe yield losses and crop failures. This study aimed to isolate weak CMV strains from natural populations of cayenne pepper, characterize their molecular properties, and evaluate the effectiveness of cross-protection conferred by weak strains against superinfection by virulent CMV strains. The research was conducted in three stages: virus isolation, molecular characterization, and evaluation of cross-protection effectiveness. Data analysis was performed using the MEGA v.11.0.11 software and analysis of variance (ANOVA). The findings identified the C1 isolate as a highly virulent CMV strain. Molecular analysis of naturally infected samples confirmed the presence of CMV through the amplification of specific DNA bands. Inoculation tests revealed distinct differences between weak and malignant strains, particularly in symptom severity and molecular characteristics, such as genetic distance. Furthermore, the weak strains demonstrated a protective effect, significantly reducing the infection rate of virulent CMV strains. This was evidenced by variations in symptom expression, disease severity, plant resistance, chlorophyll levels, carbohydrate content, and peroxidase enzyme activity. These findings highlight the potential application of weak CMV strains in developing disease management strategies for cayenne pepper cultivation.